Free radical scavenging capacity and modulative effect on antioxidant enzyme activity of Pluchea indica Less. tea leaf extract - Thoobbucha, Naruemon; Petchler, Chatchawin (Health Science, Science and Technology Reviews, 2015)
The aim of the present study is to investigate the free radical scavenging and modulative effect on the antioxidant enzyme activity of Pluchea indica Less. tea leaf extract. Superoxide and hydroxyl radical scavenging activities were measured. The result showed that the percentage of free radical inhibition markedly increased both on superoxide and hydroxyl radicals in concentration-dependent manners. IC50 levels against superoxide and hydroxyl radicals were 265.84 ± 20.55 μg/mL, and 161.91 ± 4.94 μg/mL, respectively. Moreover, the activities of 1 unit/mL of catalase (CAT) and glutathione peroxidase (GPx) were assayed with different concentrations of the extract for 30 minute incubation. The increase of catalase activity in a concentration-dependent profile was observed but it did not alter in case of glutathione peroxidase activity.